Analisis Kinerja Keuangan Perusahaan Dengan Menggunakan Metode EVA (Economic Value Added) - Maulidiah, Anita; Nasution, Ute Chairuz (Jurnal Dinamika Administrasi Bisnis, 2017)
This study is an analysis of the PT. Bank CIMB Niaga Tbk with title "Financial Performance Analysis Method Using EVA (Economic Value Added)".The purpose of this study was to apply the EVA method to measure the financial performance, and want to know whether the application of EVA method can generate economic added value in the company.               The analytical tool used to assess the financial performance at PT. Bank CIMB Niaga Tbk using EVA (Economic Value Added) is a means of assessing the financial performance of companies that pay attention to fair expectations of the funders (creditors and shareholders). While the steps in analyzing the data include: (1) calculate the net profit after tax (NOPAT), (2) calculate the total capital generated (Invest Capital), (3) calculate the cost of capital weighted average (WACC), (4) calculates the cost of capital (capital charges), and (5) calculate Economic Value Added EVA is equal to NOPAT - capital charges.               Standardized assessment of financial performance with the EVA method is if the company has EVA> 0 then there has been a value added to the company, while if EVA = 0 indicates the breakeven position and vice versa if EVA <0 indicates a process of adding value to the company.       The results of the calculation method of EVA, the company's financial performance can be measured. The results of calculations with the analysis of EVA PT. Bank CIMB Niaga Tbk in 2011 EVA amounted to 2,332,006, in 2012 the value of EVA amounted to 2,381,846, in 2013 the value of EVA amounted to 2,330,302, in 2014 amounted to 415 681 EVA showed satisfactory economic added value despite the drop and rise, though performance can be good company in managing its working capital because of the value generated positive EVA. Whereas in 2015 the value of EVA amounted -1,119,213 show this year the company did not generate economic value, in this case the company's performance in bad condition. Based on the above conclusion, the writer implies that should PT. Bank CIMB Niaga Tbk and other companies that have gone public can use EVA method for measuring the company's financial performance. As for companies that have a negative EVA value, then the company should pay attention to the capital structure and reduce the level of capital costs. Keywords: Financial performance, Economic Value Added (EVA)